التعليم التعاوني وآثاره (Comprehensive Journal of Science, 2026)
This study aims to identify the types of teaching methods used in the field of education, which are numerous, and each method has its own system related to how it is implemented. One of these methods is cooperative education, which is known through Islamic education. The problem addressed by the research relates to how to benefit from cooperative education in different educational fields, what is the role of governmental institutions in helping those who carry it out, and how to advance our societies. The research is important because it highlights the role of cooperative education and is not limited to Islamic education, or in other words, it is not limited to Islamic education, i.e., religious education. The researcher used the descriptive method to study this phenomenon, as well as the analytical method to reach the desired results of the research. The researcher reached a number of results and recommendations that she indicated at the end of the research.